Social Media and Lifestyle Formation among Islamic Religious Education Students in an Indonesian Islamic University - Mawaddah Khofifah (Jurnal Pendidikan Islam, 2026)
This study analyzes the role of social media in shaping the lifestyle of Islamic Religious Education students at Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, Indonesia. The study focuses on how social media influences students’ appearance, self-expression, academic practices, social interaction, leisure activities, and time management. This research employed a descriptive qualitative approach. Data were collected through non-participant observation, semi-structured interviews with students of the Islamic Religious Education Study Program, and documentation of students’ social media-related activities. Data were analyzed through data reduction, data display, and conclusion drawing, supported by source triangulation, technique triangulation, prolonged engagement, persistent observation, and peer discussion. The findings show that social media functions not only as a means of communication and entertainment but also as a multidimensional lifestyle-forming environment. Students use social media as a reference for fashion, hijab style, self-presentation, learning materials, religious motivation, peer interaction, and leisure activities. However, social media also creates challenges, particularly in relation to online dependency, reduced face-to-face communication, trend-following behavior, and time mismanagement. The study concludes that social media shapes student lifestyle through a continuous negotiation between digital exposure, peer culture, academic needs, Islamic values, and self-control. The study implies that Islamic higher education institutions need to strengthen digital literacy and Islamic character education so that students can engage with social media critically, ethically, and productively.